2009
DOI: 10.1111/j.1365-2249.2009.03922.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased numbers of circulating plasmablasts and differences in IgA1-plasmablast homing to skin in coeliac disease and dermatitis herpetiformis

Abstract: SummaryThe two clinical phenotypes of gluten enteropathy, coeliac disease (CD) and dermatitis herpetiformis (DH), were characterized for numbers and homing profiles of circulating final effector B cells, plasmablasts, identified as immunoglobulin (Ig)-secreting cells (ISC). In CD, the numbers of ISC were~50% lower than in DH or controls. ISC expressed peripheral lymph node homing receptor (HR), L-selectin, less frequently in CD (54%) and DH (52%) patients than in controls (70%). The expression of gut mucosal H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
(84 reference statements)
2
4
0
1
Order By: Relevance
“…In line with previous data [32], the expression of CD62L, a late activation marker was lower than normal in CD. On the other hand, lymphocytes with early activation marker CD69 were more prevalent as in previous reports [7,10,13], while the prevalence of CD4 ?…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous data [32], the expression of CD62L, a late activation marker was lower than normal in CD. On the other hand, lymphocytes with early activation marker CD69 were more prevalent as in previous reports [7,10,13], while the prevalence of CD4 ?…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, CD patients do not have IgA1, what may be evidence of selective entrapment of blood mononuclear cells to the DH skin [39]. Thus, plausibly IgA in the skin of DH patients is not produced in the gut or alternatively if it shows gut-mediated production, then only IgA1 is involved in the formation of cutaneous lesions [40], which might support our thesis of the importance of local factors in DH manifestation. Moreover, a local inflammatory process in the presence of IgA1 deposits at the DEJ would allow for the rolling and tethering of neutrophils to firmly adhere to vessel walls and move to the DEJ with resultant characteristic skin lesions [7].…”
Section: Discussionsupporting
confidence: 61%
“…Cutaneous IgA in DH consisted of both IgA1 and IgA2, although IgA1 predominated, however there are data about findings of IgA1 alone in the DH skin [39]. A recent study has also shown the increased skin-homing potential of IgA1-plasmablast compared with IgA2 cells in DH [40], what may be related with previous papers that demonstrated IgA1 deposits in the skin of DH patients [41,42]. Therefore, presented findings suggest that an increased skin-homing potential of IgA1 cells compared with IgA2 cells in DH could contribute to the formation of IgA1 deposits in the skin of DH patients.…”
Section: Discussionmentioning
confidence: 99%
“…To evade the protective effect of S-IgA at the mucosal sites, some pathogenic bacteria (e.g., Streptococcus pneumoniae, Haemophilus influenzae, Neisseria meningitidis, and Neisseria gonorrhoeae) produce proteases which cleave the IgA1 molecule (31), leaving the IgA2 intact. The unequal distribution of IgA subclasses in different body fluids (5,13,28) and among IgA-secreting cells in the circulation (25) and mucosal and systemic lymphoid tissues (11,30) has been reported in several independent studies. The differential distribution of the two IgA subclasses in secretions has been shown to be accompanied by a similar distribution of IgA1-and IgA2-producing cells at those sites (11,30).…”
mentioning
confidence: 91%